Analysis and potential use of Google Trends as a monitoring tool for risk communication during COVID-19 pandemic - Nindya Mahfuza; Rizma Adlia Syakurah; Resiana Citra (International Journal of Public Health Science (IJPHS), 2020)
COVID-19 Pandemic has become a major problem in various infected countries, including Indonesia. The proper risk communication strategy during this outbreak was important to reduce the impact. Therefore, this research was intended to assess the potential use of Google Trends as a tool to monitor risk communication during COVID-19 pandemic in Indonesia. Search patterns were analyzed using the terminology used to identify COVID-19 in Indonesia, followed by information-finding keywords 'gejala (symptoms)', 'mencegah (preventing)', and 'obat (drug)' keywords compared to the number of newly confirmed COVID-19 cases in Indonesia using time-lagged correlation analysis from December 31th, 2019 to April 20th, 2020. Peaks within respective timelines were qualitatively described according to current COVID-19 related events. ”Corona” was the terminology mostly used in Indonesia to identify COVID-19. There were five spikes observed from “corona” keyword timeline, which each spike was dependent on the media coverage and regulation by the Government. Validation using time-lagged correlation yields significant results between corona, corona symptoms, preventing corona and corona drugs compared to newly confirmed COVID-19 cases in Indonesia. Google Trends can potentially be used to maximize the improvement of risk communication and as a tool to monitor public restlessness during the COVID-19 pandemic in Indonesia by Government.